Theological Reflections on Naomi’s Shrewdness - Hubbard, Robert L. (Tyndale bulletin, 1989)
This paper probes questions about divine providence and human initiative through reflection on Naomi's plan as seen in the context of Yahweh's actions in the book of Ruth.